2023
DOI: 10.3390/biomedicines11041182
|View full text |Cite
|
Sign up to set email alerts
|

From Interaction to Intervention: How Mesenchymal Stem Cells Affect and Target Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) lacks estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 expressions, making targeted therapies ineffective. Mesenchymal stem cells (MSCs) have emerged as a promising approach for TNBC treatment by modulating the tumor microenvironment (TME) and interacting with cancer cells. This review aims to comprehensively overview the role of MSCs in TNBC treatment, including their mechanisms of action and application strategies. We analyze the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Breast cancer is the most common malignant tumor in women and has become a serious public health problem in the world today. It has been reported that cancer stem cells are the pivotal cause of malignant tumors [ 1 , 2 ]. BCSCs are the origin of breast cancer, causing tumors to grow or form new tumor focus.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common malignant tumor in women and has become a serious public health problem in the world today. It has been reported that cancer stem cells are the pivotal cause of malignant tumors [ 1 , 2 ]. BCSCs are the origin of breast cancer, causing tumors to grow or form new tumor focus.…”
Section: Introductionmentioning
confidence: 99%